Sequencing innovation rollout: Learning opportunity versus entry speed - Klingebiel, Ronald; Joseph, John; Machoba, Valerie (Strategic Management Journal, 2022)
Abstract Research summary Our article examines the deliberate creation of learning opportunities in the global rollout of innovations. Some firms launch in only a subset of markets at first, with later launches being conditional on debut‐market performance. Such sequencing decreases the downside of potential innovation failure but increases the downside of potential competitive preemption. Consistent with this trade‐off, handset makers during the feature‐phone era sequence rollout more often when innovations are novel. Also consistent is that sequencing seems to respond to firms' past experience with failure and preemption, and that it begins in markets offering strong signals of success and failure—markets with competing innovations and sophisticated consumers, respectively. Our findings contribute to the understanding of entry strategy and opens avenues for researching intentional organizational experimentation. Managerial summary Firms can decide whether to launch innovations little by little or everywhere at once. Trial launches allow firms to test commercial viability and react to outcomes before rolling out elsewhere, but risks that competitors get their first. An immediate global launch, by contrast, reduces the scope for competitive preemption but increases the costs of potential failure. Our article uses data from the handset industry to highlight conditions that shape rollout decisions and examine the debut markets sought out for trial launches. Firms tend to trial novel innovations in particular, and their experience with prior misses as well as flops influences their preference. Trial launches often begin in markets with strong competition and discerning consumers, indicating an initial prioritization of learning over monetization. Opportunities for experimentation during market rollout thus ought to feature in strategic considerations of entry timing.